Os efeitos do discurso : uma análise de cartas publicitárias - Patriota, Rosinere Pires (2010)
This dissertation speaks about on the discursive analysis of letters advertising executives who arrive at the residence, the luggage-direct calls. The research uses the theory developed for the French school of discursive Analysis, more specifically, the appreciation of discursive formation, also uses the conception to the same effect, landslide, beyond the understanding of imaginary formation. The concept of persuasive speech helps to complement it this research, whose objective to analyze the persuasive speeches of letters advertising executives and the effect of felt as well as examining the conditions of production of the letters advertising executives and observing as this speech inside produces effect of sensible of each discursive formation. Thus, this work intends to analyze the persuasive speeches of letters advertising executives and its effect of felt in the purchase and to sell. The employed methodology was the collect of the letters that arrived at the residence and the house of friends. Later, six letters had been chosen, five envelopes and one coupon to be examined. The selected companies had been treated by us with fictitious names: one works with the segment of magazines, to another one with purchase of books, four is companies of credit cards and, finally, we analyze the letter of a religious institution catholic. The reason of the choices of these companies must, in first place, to the representation of these letters in the universe of the letters advertising executives and to its variety. Another reason was that the company who purchase reviewed has an annual work to carry through a drawing being objectified to stimulate the customer to continue signing the magazine for plus one year. The book company is one of magazines and uses to advantage the subscribers of the magazine to vender books of varieties. The companies of cards, B and C are organizations that possess the same ideological discursive formation/and the objective is to vender its services of credit. The religious institution, in turn, sends one annually the rosary and asks for contribution for it, and continues, throughout the year, ordering on letters and products to the religion and asking for contributions for them. The letters generate an effect of sensible of that the consumer is always earning and not buying. It has a effect of a relation between friends, with the landslide of the directions between stimulation of consumption and to make businesses for the construction of affective bonds and attainment of good